IMPLEMENTATION OF REGIONAL SPATIAL PLANNING (RTRW) REGULATIONS IN PREPARING LONG-TERM AND MEDIUM-TERM DEVELOPMENT PLANS IN MEDAN CITY - Yahya Naufal Hawari; Abdiyanto; Abdi Sugiarto (Bulletin of Engineering Science, Technology and Industry, 2024)
This research explains howImplementation of Regional Spatial Planning (RTRW) Regulations in Preparing Long-Term and Medium-Term Development Plans in Medan City. The type of research used in this research is qualitative research and literature study. The approach that will be taken in this research is to use a qualitative descriptive approach. This method can also be used by describing the data that has been collected and then comparing it to look for correlations. Data collection techniques are methods used to obtain the data needed in research using certain techniques. The results of research on Regional Regulations on Regional Spatial Planning (RTRW) according to Law Number 26 of 2007 through the Implementation of National Spatial Planning to create a safe, comfortable, productive and sustainable archipelagic space, mandate that implementing regulations be formed as an operational basis for implementing the provisions -the provisions of the Law. After the spatial plan for the Medan city area is stipulated in a Regional Regulation, it is then used as a guideline in preparing long-term regional development plans, preparing medium-term regional development plans, space utilization and controlling space utilization in the Medan city area as well as realizing integration, linkage and balance between sector, determining the location and function of space for investment, spatial planning of the strategic area of ​​Medan city. Inhibiting factors in the Regional Spatial Planning in Medan City are physical problems of land that is not suitable for its intended use, environmental carrying capacity, the level of concern of law enforcement officials, and limited human resources and a community culture that still does not care about the environment. The increase in the number of settlements will have a serious impact on the sustainability and balance of this region.